ChatGPT: Revolution communication in crisis situations - Gligora, Tomislav (Crisis Management Days, 2024)
Chat Generative Pre-trained Transformer (ChatGPT) is a free-use artificial intelligence (AI) chatbot. Developed by OpenAI, it was trained on 570 gigabytes of data and over 300 billion words. It has the ability to generate human-like responses to user inputs and uses Reinforcement Learning with Human Feedback (RLHF) to optimize its responses (Open AI, 2023.). Machine learning algorithms utilize various techniques to enable computers to learn from data and improve their performance without being explicitly programmed. These techniques include supervised learning, unsupervised learning, and reinforcement learning, among others. By processing and analyzing data, these algorithms can make predictions, recognize patterns, and generate insights. It also learns from these interactions and can adapt its future responses to past exchanges. As an AI language model, ChatGPT has the potential to revolutionize crisis management systems and transform the way we respond to emergencies. This work discusses how ChatGPT can be effectively utilized for crisis management and how it can change the current crisis management framework. There are eight main features that can improve management in crisis situations that will be analyzed in the paper: Scalability, Availability, Speed, Cost-effectiveness, Offering emotional support, Assisting with resource allocation, Monitoring social media, Personalization